3d interaction homology: The structurally known rotamers of tyrosine derive from a surprisingly limited set of information‐rich hydropathic interaction environments described by maps. Issue 6 (June 2015) - Ahmed, Mostafa H.; Koparde, Vishal N.; Safo, Martin K.; Neel Scarsdale, J.; Kellogg, Glen E.
ABSTRACT Sidechain rotamer libraries are obtained through exhaustive statistical analysis of existing crystallographic structures of proteins and have been applied in multiple aspects of structural biology, for example, crystallography of relatively low‐resolution structures, in homology model building and in biomolecular NMR. Little is known, however, about the driving forces that lead to the preference or suitability of one rotamer over another. Construction of 3D hydropathic interaction maps for nearly 30, 000 tyrosines reveals the environment around each, in terms of hydrophobic (π–π stacking, etc.) and polar (hydrogen bonding, etc.) interactions. After partitioning the tyrosines into backbone‐dependent (ϕ, ψ) bins, a map similarity metric based on the correlation coefficient was applied to each map‐map pair to build matrices suitable for clustering with k‐means. The first bin (−200° ≤ ϕ < –155°; −205° ≤ ψ < –160°), representing 631 tyrosines, reduced to 14 unique hydropathic environments, with most diversity arising from favorable hydrophobic interactions with many different residue partner types. Polar interactions for tyrosine include surprisingly ubiquitous hydrogen bonding with the phenolic OH and a handful of unique environments surrounding the tyrosine backbone. The memberships of all but one of the 14 environments are dominated (>50%) by a single χ1/χ2 rotamer. The last environment has weak or no interactions with the tyrosine ring and its χ1/χ2 rotamer is indeterminate, which is consistent with it being composed of mostly surface residues. Each tyrosine residue attempts to fulfill its hydropathic valence and thus, structural water molecules are seen in a variety of roles throughout protein structure. Proteins 2015; 83:1118–1136. © 2015 Wiley Periodicals, Inc.